An Analysis of Students' Anxiety in Online English Learning during the COVID-19 Outbreak - Andi Irlina; Ajri Khairani (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2022)
There are several factors that affect students' anxiety when learning English online. Students' anxiety affected their performance in online English learning. The purpose of the research is to find out the factors that caused students' anxiety about learning English online, and to find out the students' understanding about learning English online. The researcher was interested in finding out what factors caused anxiety in students while learning English online. The author used descriptive qualitative research to investigate the factors that caused students' anxiety and students' perceptions of online English learning in this study. It explains the factors that affect MAN 2 Tabalong students. The researcher uses three techniques to collect data. There are observations, interviews and documentation. The researchers also use an interactive analysis model to analyze the data. Observations were conducted in online classes and offline class XI MIA 2 MAN 2 Tabalong. Six students and one English teacher were then interviewed face to face. The researcher concluded that there are two types of factors, internal and external, that affect the anxiety of Class XII MIA 2 students. the result showed that there are internal factors and 5 external factors. The findings of the study revealed that the majority of students held a negative perception towards learning English online